Effect of treatment with interferon beta-1a on changes in voxel-wise magnetization transfer ratio in normal appearing brain tissue and lesions of patients with relapsing-remitting multiple sclerosis: a 24-week, controlled pilot study. - Robert Zivadinov; Michael G Dwyer; Silva Markovic-Plese; Cheryl Kennedy; Niels Bergsland; Deepa P Ramasamy; Jacqueline Durfee; David Hojnacki; Brooke Hayward; Fernando Dangond; Bianca Weinstock-Guttman (PLoS ONE, 2014)
Background This pilot study investigated changes in remyelinating and demyelinating activity in normal appearing brain tissue (NABT) and lesions, by using voxel-wise magnetization transfer ratio (VW-MTR), in patients with relapsing-remitting multiple sclerosis (RRMS) receiving interferon beta-1a 44 mcg subcutaneously (IFN β-1a SC) three times weekly versus healthy controls (HCs) (NCT01085318). Methods Increasing (suggestive of remyelination) and decreasing (suggestive of demyelination) VW-MTR changes in NABT and in T2, T1 and gadolinium (Gd)-enhancing lesion volume were measured over 24 weeks in 23 patients treated with IFN β-1a SC and in 15 HCs (where applicable). VW-MTR changes were tested using the Wilcoxon signed-rank or Wilcoxon rank-sum test. Results A trend for greater volume of NABT with increasing VW-MTR at 24 weeks was observed for patients versus HCs (median [range] 1206 [0-15278]; 342 [0-951] mm3; p = 0.061). NABT volume with increasing VW-MTR at 12 weeks was significantly greater in patients than in HCs (852 [6-11577]; 360 [0-1755] mm3; p = 0.028). Similar findings were detected for lesion volumes. Two patients with notably high numbers of Gd-enhancing lesions at baseline had a markedly greater volume of tissue with increasing VW-MTR compared with other patients. Volume of NABT tissue with decreasing VW-MTR was significantly greater in patients versus HCs at 24 weeks (942 [0-6141]; 297 [0-852] mm3; p<0.001). Conclusions The significant change in NABT volume with increasing VW-MTR at 12 weeks suggests that active remyelination in patients with RRMS may occur during treatment with IFN β-1a SC. Findings from two patients with the highest number of Gd-enhancing lesions at baseline suggest that extensive remyelination in NABT may occur in patients with high disease activity. Tissue volume with decreasing VW-MTR was greater in patients than in HCs, despite treatment, validating the sensitivity of this technique for detecting MS disease activity. Trial registration ClinicalTrials.gov NCT01085318.